Social cognitive dysfunction as a clinical marker: A systematic review of meta-analyses across 30 clinical conditions. (January 2018) - Cotter, Jack; Granger, Kiri; Backx, Rosa; Hobbs, Matthew; Looi, Chung Yen; Barnett, Jennifer H.
Highlights: Social cognitive deficits are present in a wide range of clinical conditions. These are comparable in magnitude to more established neurocognitive deficits. Social cognitive deficits appear to hold both functional and clinical relevance. These are an important but frequently overlooked aspect of cognitive dysfunction. Abstract: Social cognition includes a range of cognitive processes that help individuals to understand how others think and feel. There is emerging evidence that social cognitive deficits may represent a transdiagnostic issue, potentially serving as a marker of neurological abnormality. We performed an electronic database search in order to identify published, peer-reviewed meta-analyses that compared facial emotion recognition or theory of mind task performance between individuals meeting clinical criteria for a psychiatric, neurological or developmental condition against healthy controls. We identified 31 meta-analyses eligible for inclusion that examined performance across relevant tasks among 30 different clinical populations. The results suggest that social cognitive deficits appear to be a core cognitive phenotype of many clinical conditions. Across the clinical groups, deficits in social cognitive domains were broadly similar in magnitude to those previously reported for more established aspects of cognition, such as memory and executive function. There is a need to clarify the 'real world' impact of these deficits, and to develop effective transdiagnostic interventions for those individuals that are adversely affected.